Parent-Assisted Early Literacy and Numeracy Practices: Basis for A Proposed Intervention Program - Jomboy , Lea C. (RIRAI Publisher, 2025)
Pre-reading and numeracy skills of kindergarten learners currently lack substantial scientific evidence, and continuously pose a challenge in all early childhood learning institutions. To delve into this issue, the researcher conducted a study to find out how the parent-assisted early literacy practices affected pre-reading and numeracy skills as basis for designing an intervention program. A descriptive correlational research design was used in order to attain its objectives. The respondents of the study were the parents or guardians of the kindergarten learners of the three elementary school of Esperanza II, Division of Agusan del Sur who were chosen through cluster sampling and which sample size was determined through Slovin’s formula. Self-made research instruments were used to answer the problems of the study. Mean and standard deviation were used to measure the level of parent-assisted early literacy practices, while frequency and percentage were used to describe levels of the pre-reading and numeracy skills of kindergarten learners. Moreover, significant relationships were measured using Spearman Rho correlation. The findings of the study revealed that the level of parent-assisted early literacy practices in terms of reading and numeracy were satisfactory and very satisfactory, respectively. Further, significant relationship existed between parent-assisted early literacy practices and pre-reading skills in terms of phonological awareness, and numeracy skills in terms of number knowledge, number representation, and basic operation on addition and subtraction. An intervention program was crafted based on the findings of the study.